Assessment of long-term plasma exchange for familial hypercholesterolaemia. Issue 6 (June 1980) - Thompson, G R; Myant, N B; Kilpatrick, D; Oakley, C M; Raphael, M J; Steiner, R E
Abstract : The effectiveness of repeated plasma exchange with 2 to 4 litres of plasma protein fraction as long-term treatment for familial hypercholesterolaemia has been evaluated in six severely affected patients receiving conventional cholesterol lowering treatment. Cell-separator mediated exchange at monthly intervals for one to two years reduced mean serum cholesterol levels from 18.5 mmol/l (715 mg/dl) to 12.4 mmol/l (480 mg/dl) in two female homozygotes but failed to influence xanthomata or prevent a two- to threefold increase in their left ventricular aortic systolic pressure gradients. More effective reduction of mean serum cholesterol levels from 15.7 mmol/l (608 mg/dl) to 8.6 mmol/l (333 mg/dl) in two male homozygotes by plasma exchange at fortnightly intervals for two to three years was accompanied by resolution of xanthomata and by stabilisation of aortocoronary lesions. In two male heterozygotes with angina, coronary angiographic appearances were unaltered or improved after one to two years of thrice-monthly plasma exchange, which reduced mean serum cholesterol levels from 6.4 mmol/l (248 mg/dl) to 4.7 mmol/l (182 mg/dl). We conclude that plasma exchange every one to two weeks, combined with oral nicotinic acid and/or cholestyramine, retards the rate of progression of atheroma in homozygotes and possibly induces regression in heterozygotes.